Hubungan Kualitas Pelayanan Homecare dengan Kepuasan Pasien Perawatan Luka di Rumah Sakit Bakti Timah Karimun - Vivi Padang; Utari Christya Wardhani; Sri Muharni (Journal of Educational Innovation and Public Health, 2024)
The development of home care in Indonesia has progressed to the point that many people use home care services. The epidemiological transition has resulted in an increase in the number of cases of chronic disease compared to acute disease, resulting in an increase in the number of cases of terminal disease that are not treated effectively and efficiently in hospitals. Bakti Timah Karimun Hospital has a home care service that provides several forms of services, namely wound care visits, elderly care services, baby care services, services for terminal patients, and other special needs. There are complaints from patients being managed regarding the responsiveness of the staff, friendliness and skills of the staff which are subject to evaluation. This study aims to determine the relationship between the quality of homecare services and patient satisfaction with wound care at Bakti Timah Karimun Hospital. This research is quantitative with a cross sectional study approach with a sample size of 80 people selected using total sampling techniques. The results of the study showed that the description of the quality of homecare services from the 5 components assessed (Reliability, responsiveness, assurance, empathy, and physical evidence) was in the sufficient category (73.8%), and the description of wound care patient satisfaction was in the very satisfied category. (62.5%). In this way, it is hoped that homecare nurses can improve the quality of services more optimally so that satisfaction can be achieved and maintained.